On the Design of Superstable Prestressed Frameworks - Kelly, Scott D.; Micheletti, Andrea; Tiero, Alessandro (Frontiers in Materials, 2019)
The strength and stiffness of prestressed lattices, and their mechanical behavior, depend strongly on the underlying graph and the nodal conformation geometry. A special class of structures is that of superstable frameworks, that is, prestressed frameworks which are stable independently of material properties and level of prestress. After reviewing the main related notions and results in rigidity theory, we exploit the characterization of superstability for generic configurations to establish a construction for superstable systems on a given number of nodes generically placed in two or three dimensions.